Agent-based consumer learning in e-commerce. (22nd January 2007) - Li, Xiaoqing
In the age of information and knowledge, the role of business companies is not only just to sell products and services, but also to educate their consumers. Educating consumers with extremely diversified backgrounds about technical knowledge is an important part of competitive advantage. To succeed, modern companies need to develop the best education technologies and teaching philosophies. Intelligent agents can play the right role in the personalised education of online consumers, because intelligent agents can learn the consumers' learning preferences and styles and recommend the best learning strategies. Educated and informed consumers are smarter and more confident in their buying decisions. This paper investigates using intelligent agents to support consumer learning and proposes an agent-based consumer learning support framework.